Theoretical investigation on Elastic, Thermodynamic and Optical Properties of Li3P Ionic Conductor - Hossain, M. A.; Islam, A. K. M. A. (Journal of Scientific Research, 2012)
The elastic, thermodynamic and optical properties of Li3P have been studied for the first time using the plane-wave ultrasoft pseudopotential technique which is based on the first-principles density functional theory (DFT) with generalized gradient approximation (GGA). The optimized lattice parameters, independent elastic constants, Youngs modulus E, bulk modulus B, shear modulus G, Cauchys pressure, Pughs ductility index (G/B), and Poissons ratio ? have been calculated and discussed. The temperature and pressure dependence of bulk modulus, Debye temperature, specific heats, and volume thermal expansion coefficient are all obtained through the quasi-harmonic Debye model with phononic effects for T = 0-1000 K and P = 0-35 GPa. The large reflectivity in the ultraviolet energy region between 7 13.4 eV indicates the material to be a good candidate as coating to avoid solar heating. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.12413 J. Sci. Res. 5 (1), 33-42 (2013)